Display of Counter Productive Work Behaviour in Relation to Person-Organization Fit (Global Journal of Human-Social Science, 2016)
The present study was aimed to investigate the relationship between counterproductive work behaviour CWB and person-organization fit P-O Fit within the context of manufacturing industry situated in Baddi Himachal Pradesh The sample comprised 300 employees of production department 150 male and 150 female respondents The analysis revealed that for the total sample Interpersonal Similarities 12 and unique roles 4 have contributed 16 of variance in totality for Organizational-Counterproductive Work Behaviour and for Interpersonal-Counterproductive Work Behaviour Unique Roles 4 and Value Congruence 2 contributed for 6 variance in totality In Males sample Unique Roles explained maximum variance 12 followed by Need Supplies 5 and Interpersonal Similarities 3 for Organizational-Counterproductive Work Behaviour For Interpersonal-CWB only Unique Roles have turned out to be a significant predictor which accounted for 5 of variance In Females sample Interpersonal Similarities explained maximum variance 16 followed by Demand Abilities 4 in total these predictors accounted for 20 variance for Organizational-Counterproductive Work Behaviour For Interpersonal-Counterproductive Work Behaviour Demand Abilities have explained the maximum variance 8 followed by Need Supplies 4 The results have shown the commonness of one variable viz Interpersonal Similarities in predicting Organizational-Counterproductive Work Behaviour of both the genders Further t-test revealed no significant difference between males and females on the variables of Value Congruence Need Supplies Demand Abilities Interpersonal Similarity Unique Roles Organizational and Interpersonal-Counterproductive Work Behaviour
Keywords: organizational counterproductive work behaviour (CWB-O); interpersonal counterproductive work behaviour (CWB-I) and person-organization fit (P-O Fit)